2019
DOI: 10.1080/00981389.2019.1619116
|View full text |Cite
|
Sign up to set email alerts
|

Health reform under the patient protection and Affordable Care Act: characteristics of exchange-based health insurance enrollees

Abstract: The Affordable Care Act (ACA) reformed and expanded healthcare coverage with an exchangebased health insurance program. While millions of Americans have benefited from enrollment in ACA marketplace insurance plans, many individuals are likely to be affected by potential future policy changes. Since few studies on the features of marketplace enrollees exist, we adopted a retrospective, cross-sectional study design using 2016 National Health Interview data to identify sociodemographic and health characteristics … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 33 publications
(37 reference statements)
0
4
0
Order By: Relevance
“…In addition, because health insurance may be associated not only with health but also with capacity to work, 20,21 such health insurance concerns may be associated with whether adults aged 50 to 64 years feel flexibility to change jobs or retire, both directly and indirectly. 25 and that this proportion grew between 2013 and 2015. 1 In addition to concerns about affordability of health insurance, 14.1% of adults aged 50 to 64 years reported keeping a job specifically to have employer-sponsored health insurance, a phenomenon known as "job lock," whereas 11.4% reported delaying or considering delaying retirement to maintain employer-sponsored health insurance.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…In addition, because health insurance may be associated not only with health but also with capacity to work, 20,21 such health insurance concerns may be associated with whether adults aged 50 to 64 years feel flexibility to change jobs or retire, both directly and indirectly. 25 and that this proportion grew between 2013 and 2015. 1 In addition to concerns about affordability of health insurance, 14.1% of adults aged 50 to 64 years reported keeping a job specifically to have employer-sponsored health insurance, a phenomenon known as "job lock," whereas 11.4% reported delaying or considering delaying retirement to maintain employer-sponsored health insurance.…”
Section: Discussionmentioning
confidence: 93%
“…Likewise, adults aged 50 to 64 years may worry about transitions between employer-sponsored insurance plans, or from employer-sponsored insurance to Medicaid or Marketplace plans. In fact, prior studies of adults in their 50s and 60s have found that they are more likely to be enrolled in Marketplace plans compared with younger adults, 25 and that this proportion grew between 2013 and 2015. 1 In addition to concerns about affordability of health insurance, 14.1% of adults aged 50 to 64 years reported keeping a job specifically to have employer-sponsored health insurance, a phenomenon known as "job lock," whereas 11.4% reported delaying or considering delaying retirement to maintain employer-sponsored health insurance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Through a deeper understanding of nursing students' perceptions of smoking behavior, it is hoped that it can produce significant implications in efforts to prevent and treat smoking behavior in society [16], [17]. The implications of this research can include the development of health education programs that are more effective and relevant to actual needs in the field [18].…”
Section: Introductionmentioning
confidence: 99%